Pengaruh Good Corporate Governance Terhadap Nilai Perusahaan Dengan Profitabilitas Sebagai Variabel Moderasi Pada Perusahaan Food And Baverage Yang Terdaftar Di BEI Tahun 2017-2021 - Lia Fatra Nurmaula; Sunarto Sunarto (Journal of Economic, Bussines and Accounting (COSTING), 2023)
This research was conducted to find out and analyze the effect of Good Corporate on firm value with profitability as a moderating variable. The population used in this study are food and beverage companies listed on the IDX in 2017-2021. The sample was determined using a purposive sampling method and a sample of 120 was obtained. The type of data used in this study was secondary data obtained from www.idx.co.id. Data analysis was carried out using descriptive statistics, testing the SPSS version 16.0 program. The results of the study found that Institutional Ownership and Audit Committee have no effect on firm value, Managerial Ownership, Institutional Ownership, and Audit Committee moderated by profitability (ROA) have no effect on firm value. While Managerial Ownership affects the value of the company. Keywords: Managerial Ownership, Institutional Ownership, Audit Committee, Profitability, Firm Value